ダイ44ジ ナンキョク チイキ カンソクタイ ドームフジ カンソク キョテン エットウ ホウコク 2003-2004 - 大日方, 一夫; オビナタ, イチオ; Obinata, Ichio (2005)
P(論文) 第44次南極地域観測隊ドームふじ越冬隊の8名は2003年1月19日から2004年1月23日までドームふじ観測拠点(77°19S, 39°42E, 3810m a.s.l.)において越冬観測を行った.ドームふじでの越冬は,第I期南極氷床深層掘削計画の第36,37,38次隊以来の4回目であった. 今回の越冬は気象,雪氷,医学研究等の他に初めて宙空隊員が越冬し,流星バースト通信実験やオーロラ観測を行い,各分野とも貴重な結果を得ることができた. また,今回の最大の任務は第II期同計画のための新掘削場を完成させ,越冬明けの春に航空機で内陸に到着する第45次隊の5名を迎え入れて深層掘削を開始することであった.期間中大きな怪我や事故もなく無事に越冬を完了し,新掘削場,新型ドリルも予定通りに完成し,362m深まで掘削することができた. The 44th Dome Fuji Wintering party, consisting of eight personnel, carried out observation and logistic works at Dome Fuji Station (77°19S, 39°42E, 3810m a.s.l.) from 19 January 2003 to 23 January 2004. It was the 4th wintering after the 36th, 37th and 38th Japanese Antarctic Research Expedition (JARE) parties during Deep Ice Coring Project I. Meteorological, glaciological and human physiological research were done as same as the past wintering, and observations of upper atmosphere physics were carried out for the first time. Many valuable results were achieved in each field of research. Our most important duty during wintering was to complete construction of a new ice coring site during wintering for Deep Ice Coring Project II and to start drilling with five members of the 45th summer drilling team which arrived at the inland station by airplane without using a ship from Japan for the first time in the history of JARE. There was neither a major injury nor accident during wintering. We safely completed construction of the new drilling site according to schedule and we conducted the first season's deep ice core drilling of the Project II to a depth of 362m at last. departmental bulletin paper